Seroprevalence of Rickettsial Infections in Northeast India: A Population-Based Cross-Sectional Survey. (July 2021) - Khan, Siraj A.; Murhekar, Manoj V.; Bora, Trishna; Kumar, Santhosh; Saikia, Jahnabi; Kamaraj, P.; Sabarinanthan, R.
A cross-sectional survey was undertaken to estimate seroprevalence of immunoglobulin G antibodies against scrub typhus, spotted fever group rickettsiae, and typhus group rickettsiae in randomly selected 48 clusters in 12 districts of 3 Northeast states of India: Assam, Meghalaya, and Tripura. Individuals in 3 age groups (5-8, 9-17, and 18-45 years) were selected from each cluster. Sera (N = 2360) tested were collected as part of a national survey on dengue seroprevalence conducted between September 2017 and February 2018. Overall, seroprevalence of 2.5% was detected against rickettsioses, with highest positivity against spotted fever group rickettsiae, followed by scrub typhus and typhus group rickettsiae. Seroprevalence was highest in Tripura (3.7%), followed by Assam (2.6%) and Meghalaya (1.04%). Adults of 18 to 45 years of age were found to be most affected (3.8%). The study findings indicate the need for increasing testing facilities for active case detection at hospital levels. Efforts on implementing effective preventing strategies are suggested to be targeted in disease-specific endemic foci.